2021
DOI: 10.1111/aej.12570
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effects of various endodontic irrigants on the viability of dental mesenchymal stem cells

Abstract: This study aimed to evaluate cytotoxic effects of various irrigation solutions used in regenerative endodontic treatments (RETs) on mesenchymal stem cells, and further examine the long-term effect of hypochlorous acid (HOCl) on the cell viability and alkaline phosphatase (ALP) activity. Stem cells were exposed to various concentrations of NaOCl, EDTA, chlorhexidine (CHX), etidronic acid (HEDP)/NaOCl combination and HOCl. HOCl was tested for its effects on ALP activity up to 21 days. Additionally, cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
10
1
1
Order By: Relevance
“…But this should be also related to other antiseptics commonly used in dental therapy. Low concentrated NaOCl (0.05%) did not affect dental mesenchymal stem cell survival after 10 min, whereas low concentrated CHX (0.02%) caused a strong cytotoxicity [ 32 ]. Further, computational prediction did not find any mutagenic, tumorigenic irritant and reproductive toxicity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…But this should be also related to other antiseptics commonly used in dental therapy. Low concentrated NaOCl (0.05%) did not affect dental mesenchymal stem cell survival after 10 min, whereas low concentrated CHX (0.02%) caused a strong cytotoxicity [ 32 ]. Further, computational prediction did not find any mutagenic, tumorigenic irritant and reproductive toxicity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a strong oxidizing agent, NaOCl is cytotoxic to the periapical tissue and stem cells, especially in case of regenerative endodontic treatment [199]. The cytotoxic effect to dental stem cells was reported to be concentration dependent [115,200]. Furthermore, Martin et al [201] found that dentin conditioning with 1.5% NaOCl resulted in greater survival and differentiation of stem cells of apical papilla compared to the 3% counterpart, whereas 6% NaOCl leads to lack of survival and differentiation.…”
Section: Side Effectmentioning
confidence: 99%
“…Moreover, natural molecules are used in oral environment such as polyphenols, which have biological benefits as they are natural antibacterial and antioxidant molecules ( 95 ). These different materials are made commercially available in dental market and used worldwide even though they sometimes display cytotoxicity ( 96 ).…”
Section: The Involvement Of the Amps Released From The Adrenal Medull...mentioning
confidence: 99%